Challenges and importance of Environmental Education in the education system in Portugal - Tiago, Elsa; Rodrigues, Rute; Ramos, Ricardo (Revista Brasileira de Educação Ambiental (RevBEA), 2021)
The present work aims to analyze themes that address the importance of Environmental Education, in schools, today, facing the problems of the contemporary world. There is a consensus around the importance of Environmental Education in the school community, which requires environmental training for citizens and also training that better trains professionals linked to education. Sometimes the current model of Environmental Education seems to be deficient and does not satisfy the current training needs, either due to the lack of qualified teachers and the ability to articulate the set of knowledge, attitudes and environmental sensitivity in the existing disciplines. This article seeks to discuss the challenges of Environmental Education as a transversal theme in Portuguese reality.